Violent narco-cartels or US hegemony? the political economy of the 'war on drugs' in Mexico - Mercille, Julien (2011)
Offers the interpretation that the US shares much responsibilty for the drug trafficking and the related violence in Mexico due to its large drug consumption, loose firearms regulations, its record of support for the Mexico government and military, and by implementing neoliberal reforms that the increased the size of the narcotics industry.